Revisiting the ability of Australian primary healthcare services to respond to health inequity - Freeman, T.; Baum, F.; Lawless, A.; Javanparast, S.; Jolley, G.; Labonté, R.; Bentley, M.; Boffa, John; Sanders, D. (C S I R O Publishing, 2016)
© 2016 La Trobe University. Equity of access and reducing health inequities are key objectives of comprehensive primary health care. However, the supports required to target equity are fragile and vulnerable to changes in the fiscal and political environment. Six Australian primary healthcare services, five in South Australia and one in the Northern Territory, were followed over 5 years (2009-2013) of considerable change. Fifty-five interviews were conducted with service managers, staff, regional health executives and health department representatives in 2013 to examine how the changes had affected their practice regarding equity of access and responding to health inequity. At the four state government services, seven of 10 previously identified strategies for equity of access and services' scope to facilitate access to other health services and to act on the social determinants of health inequity were now compromised or reduced in some way as a result of the changing policy environment. There was a mix of positive and negative changes at the non-government organisation. The community-controlled service increased their breadth of strategies used to address health equity. These different trajectories suggest the value of community governance, and highlight the need to monitor equity performance and advocate for the importance of health equity.